ANALYSIS OF THE ABILITIES OF TERBUKA UNIVERSITY STUDENTS IN SUMMARY OF MODULE YEAR 2020/2021 (Study of Student of Science Semester 1 UT Medan) - Kula Ginting (Sensei International Journal of Education and Linguistic, 2021)
The problem examined in this study is to determine the ability of UT students to summarize a reading in the lecture module. The problem that arises is the lack of students' ability to summarize the module. The population in this study were all 1st semester PGSD students in the field of UT Medan. This type of research is quantitative research in which this research is used to examine a particular population or sample, with sampling generally carried out randomly, data collection using research instruments, data analysis is quantitative or statistical in order to test the hypothesis that has been applied.